Exploring Plan of Care Communication With a Multidisciplinary Rounding Plan to Nursing Care Plans. Issue 2 (April 2023) - Perera, Anjali C.; Joseph, Sonia; Marshall, Jade L.; Olson, DaiWai M.
ABSTRACT: BACKGROUND: The nursing care plan (NCP) was developed approximately 100 years ago as a teaching tool for nursing students. Our neuroscience intensive care unit (NSICU) uses a multidisciplinary rounding plan (MDRP) that may provide more relevant and up-to-date information than the standard NCP. METHODS: In this prospective single-blind randomized pilot study, we examined nurses' abilities to respond to 7 clinical scenarios common to the NSICU. The NCPs and MDRPs from 70 patients were randomly assigned to 14 nurses (10 per nurse) who answered each of the 7 questions using only data from an NCP or data from an MDR. RESULTS: The MDRP mean score of 4.51 (1.50) correct answers was statistically significantly higher than the NCP mean score of 0.31 (0.71) correct answer ( P < .0001). CONCLUSION: The MDRP was designed to address the modern-day communication needs of NSICU staff by leveraging technological advances. Data from this study suggest that the MDRP may have advantages over the NCP in providing contextually relevant information. Additional research is warranted to develop the MDRP as a replacement for the NCP in the NSICU setting.